Psalm 102.13-23: Qualifications Rather Than Actions. Issue 2 (August 2019) - van Wolde, Ellen
In Psalm 102 semantic contrasts abound, as is widely acknowledged in biblical scholarship. However, the contrasts on the syntactic level and on the level of the represented viewpoint have remained unnoticed, resulting in serious consequences for the translation of the tenses. The present analysis of the syntactic and narratological components of vv. 13-23 demonstrates that they express qualifications rather than actions. YHWH's sovereignty presented in v. 13 and the syntactic arrangements in vv. 14-16 identify YHWH's unique qualities: He is the one who feels compassion for Zion and his people, who rebuilds their city, and whose glory becomes perceptible for its inhabitants. The syntactic analysis also explains the uniqueness of Zion's inhabitants for him, for they are set apart from the other nations in order to praise him (v. 19). Thus the linguistic structure confirms and reinforces the psalm's understanding of a world divided into opposing realms.